Antimicrobial, immunomodulatory and tumor cells-selective cytotoxic activities of Brassica oleracea L. and Vigna radiata L - Hafidh, Rand R. (2011)
The world today faces a great challenge in the emergence of drug-resistant microbes and dangerous cancers against most of the commonly known antimicrobial and anticancer drugs, respectively. Screening for effective, new, and cheap remedies from natural resources has become the goal of many scientists all around the world. The plants’ methanol extracts used in this study were red cabbage (RC) and mung bean sprout (MBS) which both showed remarkable antiviral activities against herpes simplex virus type 1 (HSV-1) and respiratory syncytial virus (RSV). The mode of action of RC extract was shown to be prophylactic against RSV (the concentration that inhibit 50% of virus cytopathic effect (IC50) = 13.9 mg/ml and selectivity index (SI) = 17.67). Against HSV-1, RC extract showed a remarkable viricidal activity (IC50 = 11.51 mg/ml and SI = 34.52) with less prophylactic activity (IC50 = 32.97 mg/ml and SI = 11.71). MBS extract had viricidal effect (IC50 = 15.62 mg/ml and SI = 14.18), (IC50 = 7.62 mg/ml and SI = 18.23) and to a lesser extent prophylactic (IC50 = 17.23 mg/ml and SI = 12.82), (IC50 = 12.72 mg/ml and SI = 10.9) against RSV and HSV-1 viruses, respectively. One of the good explaination on the effective prophylactic activities of MBS and RC extracts was their excuisite ability to induce production of high levels of IFNβ, TNFα, IL-1, and IL-6 cytokines (300-900% higher levels when compared to untreated cells; P<0.0001) in virally infected cells. These antiviral cytokines proved to play critical and synergistic role in the antiviral resistance of human cells. For the cytotoxic effects of the tested extracts, RC extract showed selective cytotoxic effect against human cervix adenocarcinoma cells (HeLa), (SI = 10.88) while it showed less selectivity against human hepatocellular carcinoma cells (HepG2), (SI = 8.93). On the contrary, MBS extract showed a selective cytotoxic effect against both HeLa and HepG2 cells with SI values of 12.44 and 11.94, respectively. In an attempt to disclose part of the underlying mechansims of cytotoxic effect of both extracts using concentrations lower than IC50, RC induced the production of the anticancer cytokine TNFα (up to 600% increase;P<0.0001) whereas MBS induced the production of both anticancer cytokines TNFα (up to 700% increase; P<0.0001) and IFNβ (up to 300% increase; P<0.001). The increase in the anticancer cytokine levels was dose-dependent. In addition, the IC50 of RC extract induced cell cycle arrest in G0/G1 phase in cancer cells increasing the percentage of cells from 66.87 to 76.96% and from 57.83 to 70.41% in the treated HeLa and HepG2 cells, respectively. On the other hand, the IC50 of MBS extract induced cell cycle arrest in G0/G1 phase only in HeLa cells (62.87 to 80.48%). Both extracts induced remarkably apoptosis in the treated human cancer cells in a doseand time-dependent manner. The induction of apoptosis in cancerous cells 12-16h after exposure to RC and MBS extracts was significant via caspase-dependent pathways including the extrinsic pathway by upregulating caspase 8 (about 8-32 folds) and the intrinsic pathway by upregulating both caspase 9 (about 32-256 folds) and Bax genes (about 8-32 folds). Furthermore, both extracts upregulated highly caspase 7 (about 32-512 folds) which could induce apoptosis via caspaseindependent pathway. More to the point, Cdk-inhibitor proteins were upregulated (p21: about 8-512 folds, p27: about 4-16 folds, and p53: about 16-32 folds) 12-16h after exposure to both extracts and their upregulation might be the main mechanism used by both extracts to exert G1 cell cycle arrest and ultimately the final fate of cells, apoptosis. For the immunomodulatory effect of tested extracts, RC extract showed potent anti-inflammatory activity by inhibiting the production of the proinflammatory cytokine, IFNγ (about 80% decrease; P<0.01) in peripheral blood mononuclear cells (PBMC). On the other hand, MBS extract was effective immunomodulator agent as TNFα and IFNβ cytokines are also potent immunomodulators. In addition, MBS extract showed an immunopolarizing effect by inducing IFNγ (about 300% increase; P<0.01) and inhibiting IL-4 production (about 75% decrease; P<0.01) in PBMC. The immunopolarization effect of MBS extract was dose-dependent. For the antibacterial and antifungal potential of the tested extracts, antibacterial and antifungal activities against multiple drug resistant (MDR), non-MDR bacteria, and fungi were shown to be significant for both extracts. The antibacterial and antifungal activities were ose-dependent. Remarkably, antibacterial activity of RC extract was evident particularly against highly infectious microorganisms such as Methicillin-resistant Staphylococcus aureus (MRSA),Escherichia coli O157:H7, Pseudomonas aeruginosa, Klebsiella pneumoniae,Staphylococcus aureus, and Salmonella enterica serovar Typhimurium as well as against human fungal pathogens, Trichophyton rubrum and Aspergillus terreus. MBS extract revealed potential antibacterial and antifungal activities against MRSA, Escherichia coli O157:H7, Pseudomonas aeruginosa, Klebsiella pneumonaie,Staphylococcus aureus, and Salmonella Typhimurium as well as against human fungal pathogens, Trichophyton rubrum and Trichoderma harzianum. The findings of the electron microscopy together with phenotype microarray (PM) supported these results for the antibacterial activity. PM screening was a valuable tool in the search for compounds that can inhibit bacterial growth by affecting certain metabolic pathways like peptidoglycan synthesis pathway. This pathway appeared to be targeted by both RC and MBS extracts at metabolic points differ from that of other available drugs. These points could be targets for discovering new therapeutic agents for the currently studied microbes. The considerable results of this study could be explained by the powerful antioxidant activity of RC and MBS which is most likely due to the phenolic and antioxidant compounds present in these plants which act individually or synergistically to bring to light the importance of these plants as candidates for new therapeutic agents.